Effect of theory-based education on promoting a healthy lifestyle in pre-diabetic women: RCT - Kolsoum MohammadniaMotlagh; Mohsen Shamsi; Nasrin Roozbahani; Mahmood Karimi; Rahmatollah Moradzadeh (BMC, 2022)
Abstract Background Due to the fact that pre-diabetic people are at higher risk of developing diabetes, it is possible to reduce the risk by taking preventive measures. Therefore, the present study aimed to determine the effect of theory-based education on promoting a healthy lifestyle and fasting blood sugar (FBS) in pre-diabetic women. Methods This is a cluster‐randomized controlled trial that was performed on 71 pre-diabetic women referred to Arak Comprehensive Health Service Center. Thus, using cluster sampling method, one center was randomly assigned to the intervention group and one center to the control group. The data collection tool was a questionnaire based on the theory of planned behavior (TPB) and healthy lifestyle behavior that was completed before and at least 3 months after training and FBS test was performed. The experimental group received 3 training sessions of 60 to 90 min and finally the data were analyzed using statistical software. Results After the intervention, the mean scores of knowledge (P < 0.001), attitude (P = 0.047) and perceived behavioral control related to physical activity (P = 0.046) and dietary function (P = 0.01) increased significantly in the intervention group. In addition, fasting blood sugar in the intervention group (99.70 ± 11.06) improved significantly compared to the control group (110.94 ± 17.09) (P = 0.003). Conclusion Education based on the theory of planned behavior, by holding face-to-face meetings along with following up the samples after the educational intervention, can promote healthy lifestyle of pre-diabetic women. Therefore, designing and implementing similar interventions on all pre-diabetic individuals seem necessary. Trial registration: The master's thesis in health education is approved by Arak University of Medical Sciences, Iran and is registered in the Iranian Registry of Clinical Trial (IRCT20190304042921N1). Prospectively registered 22/07/2019, https://en.irct.ir/trial/40596.